2022
DOI: 10.31234/osf.io/q8t2k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidimensional signals and analytic flexibility: Estimating degrees of freedom in human speech analyses

Abstract: Recent empirical studies have highlighted the large degree of analytic flexibility in data analysis which can lead to substantially different conclusions based on the same data set. Thus, researchers have expressed their concerns that these researcher degrees of freedom might facilitate bias and can lead to claims that do not stand the test of time. Even greater flexibility is to be expected in fields in which the primary data lend themselves to a variety of possible operationalizations. The multidimensional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Additionally, the intricate multidimensional nature of the speech signal, the underlying mechanisms governing its production, and the subtleties of psychoacoustic sound perception by humans must be considered. This approach allows for the identification of latent patterns within the data, even in the presence of uncertainty from the researcher's perspective [15].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…Additionally, the intricate multidimensional nature of the speech signal, the underlying mechanisms governing its production, and the subtleties of psychoacoustic sound perception by humans must be considered. This approach allows for the identification of latent patterns within the data, even in the presence of uncertainty from the researcher's perspective [15].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…Simulations in Roettger (2019) show that these decisions can be consequential for false positive rates. A recent large collaborative study by Coretta et al (2023) found that 46 different research teams tested a single research hypothesis (relating to the acoustics of atypical modifiers in German) in a wide variety of different ways, resulting in 'at least 52 unique ways of operationalizing the acoustic signal alongside 55 unique ways of constructing the statistical model ' (p. 19). This resulted in nearly 40% of the teams reporting at least one significant finding, though the majority of the models fitted as part of the project found no reliable effects.…”
Section: Replicability and Transparency In Phoneticsmentioning
confidence: 99%
“…Authors must set aside a proportion of their research projects (in terms of time, money, and resources) to Big Team Science projects and international collaborations across multiple countries. Examples of this are plenty in psychology, including social psychology (see Bago et al, 2022;Klein et al, 2018;Moshontz et al, 2018;Pownall et al, 2021, van Bavel et al, 2022, cognitive psychology (Chen et al, 2023), linguistics (Coretta et al, 2022) and economics (Delios et al, 2022;Tierney et al, 2020Tierney et al, , 2021. Although such studies are very time-and resource-intensive, depending on the study characteristics and the role of the author, this is one benefit to ensure that our findings are universal and generalizable.…”
Section: Researchers: Data Reporting and Analysis Stagesmentioning
confidence: 99%